Hidden Lineage Complexity of Glycan-Dependent HIV-1 Broadly Neutralizing Antibodies Uncovered by Digital Panning and Native-Like gp140 Trimer - He, Linling; Lin, Xiaohe; de Val, Natalia; Saye-Francisco, Karen L.; Mann, Colin J.; Augst, Ryan; Morris, Charles D.; Azadnia, Parisa; Zhou, Bin; Sok, Devin; Ozorowski, Gabriel; Ward, Andrew B.; et al. (Frontiers in Immunology, 2017)
Germline precursors and intermediates of broadly neutralizing antibodies (bNAbs) are essential to the understanding of humoral response to HIV-1 infection and B-cell lineage vaccine design. Using a native-like gp140 trimer probe, we examined antibody libraries constructed from donor 17, the source of glycan-dependent PGT121-class bNAbs recognizing the N332 supersite on the HIV-1 envelope glycoprotein (Env). To facilitate this analysis, a digital panning method was devised that combines biopanning of phage-displayed antibody libraries, 900bp long-read next-generation sequencing (NGS), and heavy/light (H/L)-paired antibodyomics. In addition to single-chain variable fragments (scFvs) resembling the wild-type bNAbs, digital panning also identified variants of PGT124 (a member of the PGT121 class) with a unique insertion in the heavy chain complementarity-determining region 1 (HCDR1), as well as intermediates of PGT124 exhibiting notable affinity for the native-like trimer and broad HIV-1 neutralization. In a competition assay, these bNAb intermediates could effectively compete with mouse sera induced by a scaffolded BG505 gp140.681 trimer for the N332 supersite. Our study thus reveals previously unrecognized lineage complexity of the PGT121-class bNAbs and provides an array of library-derived bNAb intermediates for evaluation of immunogens containing the N332 supersite. Digital panning may prove to be a valuable tool in future studies of bNAb diversity and lineage development.